Regional zircon U-Pb geochronology for the Maniitsoq region, southwest Greenland - Olierook, Hugo K H; Kirkland, Christopher L; Hollis, Julie A; Gardiner, Nicholas J; Yakymchuk, Chris; Szilas, Kristoffer; Hartnady, Michael I H; Barham, Milo; McDonald, Bradley J; Evans, Noreen J; Steenfelt, Agnete; Waterton, Pedro (Scientific Data, 2021)
The Ministry of Mineral Resources, Government of Greenland, funded this project. Analyses in the JdLC GeoHistory Facility were enabled by instrumentation supported by AuScope (auscope.org.au) and the Australian Government via the National Collaborative Research Infrastructure Strategy. The Tescan Mira3 FEG-SEM was funded through the Australian Research Council LIEF program. Zircon U-Pb geochronology places high-temperature geological events into temporal context. Here, we present a comprehensive zircon U-Pb geochronology dataset for the Meso- to Neoarchean Maniitsoq region in southwest Greenland, which includes the Akia Terrane, Tuno Terrane, and the intervening Alanngua Complex. The magmatic and metamorphic processes recorded in these terranes straddle a key change-point in early Earth geodynamics. This dataset comprises zircon U-Pb ages for 121 samples, including 46 that are newly dated. A principal crystallization peak occurs across all three terranes at ca. 3000 Ma, with subordinate crystallization age peaks at 3200 Ma (Akia Terrane and Alanngua Complex only), 2720 Ma and 2540 Ma. Metamorphic age peaks occur at 2990 Ma, 2820-2700 Ma, 2670-2600 Ma and 2540 Ma. Except for one sample, all dated metamorphic zircon growth after the Neoarchean occurred in the Alanngua Complex or within 20 km of its boundaries. This U-Pb dataset provides an important resource for addressing Earth Science topics as diverse as crustal evolution, fluid-rock interaction and mineral deposit genesis. Peer reviewed